The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1945-5100.2011.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bunburra Rockhole meteorite fall in SW Australia: fireball trajectory, luminosity, dynamics, orbit, and impact position from photographic and photoelectric records

Abstract: Abstract-We report an analysis of the first instrumentally observed meteorite fall in Australia, which was recorded photographically and photoelectrically by two eastern stations of the Desert Fireball Network (DFN) on July 20, 2007. The meteoroid with an initial mass of 22 kg entered the atmosphere with a low speed of 13.36 km s )1 and began a luminous trajectory at an altitude of 62.83 km. In maximum, it reached )9.6 absolute magnitude and terminated after a 5.7 s and 64.7 km long flight at an altitude of 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 26 publications
6
61
0
Order By: Relevance
“…As this data resulted in a recovered meteorite, constraints are available on final mass (Spurný et al. ), and cosmic ray exposure rates (Welten et al. ) provide an estimate of initial body diameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As this data resulted in a recovered meteorite, constraints are available on final mass (Spurný et al. ), and cosmic ray exposure rates (Welten et al. ) provide an estimate of initial body diameter.…”
Section: Resultsmentioning
confidence: 99%
“…This can be obtained by the addition of a photoelectric photometer to a fireball observatory (Spurný et al. ). Not only is this an expensive piece of equipment in itself but also requires additional power supplies, which are limited in the remote locations of the DFN observatories.…”
Section: Introductionmentioning
confidence: 99%
“…The film observatories used a photomultiplier tube to obtain a light curve for each meteorite, which was used to calculate fragmentation events and derive absolute timing information. The trial network resulted in two successful meteorite recoveries [3,4], proving the viability of a meteor camera network based in the Australian Outback. The observatories used numerous custom components and moving parts in the film handling system, mechanical shutter, retractable sun shade and lens covers leading to high manufacturing and maintenance costs.…”
Section: Introductionmentioning
confidence: 82%
“…The calculated orbit for Bunburra Rockhole showed that it came from an asteroid in an Aten-type orbit (Bland et al, 2009;Spurný et al, 2012). Using a probabilistic orbital evolution model (Bottke et al, 2002), Bland et al (2009) showed that Bunburra Rockhole originated from the innermost main belt, interior to 4 Vesta and the core Vestoid family (Zappala et al, 1995).…”
Section: Anomalous Naturementioning
confidence: 99%